2015
DOI: 10.1002/jbmr.2721
|View full text |Cite
|
Sign up to set email alerts
|

Milk Fat Globule-Epidermal Growth Factor 8 (MFG-E8) Is a Novel Anti-inflammatory Factor in Rheumatoid Arthritis in Mice and Humans

Abstract: Milk fat globule-epidermal growth factor 8 (MFG-E8) is an anti-inflammatory glycoprotein that mediates the clearance of apoptotic cells and is implicated in the pathogenesis of autoimmune and inflammatory diseases. Because MFG-E8 also controls bone metabolism, we investigated its role in rheumatoid arthritis (RA), focusing on inflammation and joint destruction. The regulation of MFG-E8 by inflammation was assessed in vitro using osteoblasts, in arthritic mice and in patients with RA. K/BxN serum transfer arthr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 39 publications
1
48
1
Order By: Relevance
“…41 Also in a colitis model, MFG-E8 reduced NF-kB signaling and modulated a v b 3 integrin expression. 37 The study of Albus et al, 5 which investigated the role of MFG-E8 in rheumatoid arthritis, further underlines the observation that an inflammatory milieu reduces MFG-E8 levels. Patients suffering from rheumatoid arthritis had lower MFG-E8 serum concentrations compared with healthy controls, which rose again after complete or partial remission.…”
Section: Role In Inflammatory Diseasesmentioning
confidence: 92%
See 2 more Smart Citations
“…41 Also in a colitis model, MFG-E8 reduced NF-kB signaling and modulated a v b 3 integrin expression. 37 The study of Albus et al, 5 which investigated the role of MFG-E8 in rheumatoid arthritis, further underlines the observation that an inflammatory milieu reduces MFG-E8 levels. Patients suffering from rheumatoid arthritis had lower MFG-E8 serum concentrations compared with healthy controls, which rose again after complete or partial remission.…”
Section: Role In Inflammatory Diseasesmentioning
confidence: 92%
“…They could further show that the MFG-E8 expression in osteogenic stromal cells, which greatly contribute to the inflammatory bone loss, 42 is downregulated by LPS and TNFa. 5 This means that MFG-E8 not only regulates the inflammatory response but is also regulated by inflammatory stimuli itself 17 (Figure 1). With respect to arthritis, in which regulatory T cells have a crucial role, it is particularly interesting to notice that MFG-E8 has been implicated to control the release of TGF-b and CC chemokine ligand 22, which are both known to attract and maintain the regulatory T-cell phenotype.…”
Section: Role In Inflammatory Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…The serum level of MFG-E8 was found to be higher in SLE patients as compared to very low level in healthy controls [18]. But patients with rheumatoid arthritis showed lower serum concentrations of MFG-E8 compared with healthy controls [9]. It was reported that administration of recombinant MFG-E8 suppressed the ischemia-reperfusion induced inflammation in mouse [19].…”
Section: Are There Any Differences Between Preeclamptic and Healty Prmentioning
confidence: 95%
“…Milk Fat Globule Epidermal Growth Factor-8 (MFG-E8), a novel endometrial epithelial protein, found to have multiple biological functions against inflammation [6,7]. MFG-E8 binds to apoptotic cells, enhances the phagocytosis of apoptotic cells by macrophages and provides an anti-inflammatory function [8,9]. Topical recombinant MFG-E8 treatment induces resolution of wound inflammation, and improvement in angiogenesis [10].…”
Section: Introductionmentioning
confidence: 99%